Plan estratégico para la distribuidora de fibras textiles, CASATEX, de la ciudad de Otavalo. - Maya, Wilson O. (2021)
Casatex is a sole proprietorship, which was born into the market for the commercialization of textile products 25 years ago, as an alternative to textile producers in the province of Imbabura. During this time and thanks to a responsible and permanent work of the owners and all the employees, it has become a leading distributor in the textile market, with its high quality products from national companies, which have covered the needs of small and medium-sized artisanal and flat-woven producers. All activities have been developed in an empirical way, which is why the need to implement a Strategic Plan has been seen, which helps a better development of the company, and the achievement of administrative, financial and social objectives. For which a study of the internal reality of the company has been carried out, and to determine its operational variables, in order to establish the policies, manuals and roadmap for the next 5 years, and the start-up for one way jointly have a correct administrative performance, with a participatory work environment that allows achieving financial and economic goals and objectives.